Anti-Human Immunodeficiency Virus Antibodies in the Cerebrospinal Fluid: Evidence of Early Treatment Impact on Central Nervous System Reservoir?. (1st February 2018) - Burbelo, Peter D; Price, Richard W; Hagberg, Lars; Hatano, Hiroyu; Spudich, Serena; Deeks, Steven G; Gisslén, Magnus
Abstract : Initiation of antiretroviral therapy early after HIV infection disproportionately decreases HIV antibodies in CSF compared with blood, suggesting that early treatment may reduce the magnitude of the central nervous system HIV reservoir to a greater extent than the systemic reservoir. Abstract: Background: Despite effective antiretroviral therapy (ART), human immunodeficiency virus (HIV) likely persists in the central nervous system (CNS) in treated individuals. We examined anti-HIV antibodies in cerebrospinal fluid (CSF) and blood as markers of persistence. Methods: Human immunodeficiency virus antibodies were measured in paired CSF and serum before and after long-term treatment of chronic (n = 10) and early infection (n = 12), along with untreated early infection (n = 10). Results: Treatment of chronic infection resulted in small reductions of anti-HIV antibodies in CSF and serum despite >10 years of suppressive ART. In untreated early infection, anti-HIV antibodies emerged in blood by day 30, whereas CSF antibodies reached similar levels 2 weeks later. Compared with long-term treatment of chronic infection, early ART initiation reduced CSF antibodies by 43-fold ( P > .0001) and blood antibodies by 7-fold ( P = .0003). Two individuals receiving pre-exposure prophylaxis and then ART early after infection failed to develop antibodies in CSF or blood, whereas CSF antibodies were markedly reduced in the Berlin patient. Conclusions: To the extent that differential CSF and blood antibodies indicate HIV persistence, these data suggest a relative delay in establishment of the CNS compared with the systemic HIV reservoir that provides an opportunity for early treatment to have a greater impact on the magnitude of long-term CNS infection.